Regeneration of a keystone semiarid shrub over its range in Spain: habitat degradation overrides the positive effects of plant–animal mutualisms. (19th July 2018) - Rey, P. J.; Cancio, I.; Manzaneda, A. J.; González‐Robles, A.; Valera, F.; Salido, T.; Alcántara, J. M.
Abstract: Global change drivers are currently affecting semiarid ecosystems. Because these ecosystems differ from others in biotic and abiotic filters, cues for plant regeneration and management derived from elsewhere may not be applicable to semiarid ecosystems. We sought to determine the extent to which regional variation in regeneration prospects of a long‐lived semiarid keystone shrub depends on anthropogenic habitat degradation, plant–animal interactions and climate determinants. We investigated the regeneration ability ( via population size structure, juvenile density and juvenile/adult ratio), fruit set and seed dispersal of Ziziphus lotus in 25 localities spanning the range of its threatened habitats in Spain. We dissected the relative contribution of different regeneration determinants using multiple regression and structural equation modelling. Population regeneration was extremely poor, and size structures were biased towards large classes and low juvenile densities and juvenile/adult ratios. Poor regeneration was often coincident with seed dispersal collapse. However, the positive effect of seed dispersal on population regeneration disappeared after considering its relationship with habitat degradation. Protected areas did have juveniles. Together, these data suggest that habitat degradation directly impacts juvenile establishment. Our results provide insights into habitat and species management at the regional level. Z. lotus populations are currently driven by persistence‐based dynamics through the longevity of the species. Nonetheless, collapsed seed dispersal, poor regeneration and the removal of adults from their habitats forecast extinction of Z. lotus in many remnants. The extreme longevity of Z. lotus provides opportunities for recovery of its populations and habitats through effective enforcement of regulations.